Dropping Out, Being Pushed Out or Can't Get in? Decoding Declining Labour Force Participation of Indian Women - Ashwini Deshpande; Jitendra Singh (Institute of Labor Economics (IZA), 2021)
The stubbornly low and declining level of labor force participation rate (LFPR) of Indian women has prompted a great deal of attention with a focus on factors constraining women's labour supply. Using 12 rounds of a high frequency household panel survey, we demonstrate volatility in Indian women's labour market engagement, as they exit and (re)enter the labor force multiple times over short period for reasons unrelated to marriage, child-birth, or change in household income. We demonstrate how these frequent transitions exacerbate the issue of measurement of female LFPR. Women elsewhere in the world face a "motherhood penalty" in the form of adverse labour market outcomes after the first childbirth. We evaluate the motherhood penalty in the Indian context and find that mothers with new children have a lower base level of LFPR, but there is no sharp decline around the time of childbirth. Blinder-Oaxaca decomposition of determinants of female LFPR suggests that none of the total fall (10 percentage points) in our study period is explained by a change in supply-side demographic characteristics. We suggest that frequent transitions, as well as fall in LFPR, are consistent with the demand-side constraints, viz., that women's participation is falling due unavailability of steady gainful employment. The high unemployment rate and industry-wise composition of total employment provide suggestive evidence that women's participation is falling as women are likely to be displaced from employment by male workers. We show that women's employment is likely to suffer more than men's due to negative economic shocks, as was seen during the fallout of demonetisation of 86 percent of Indian currency in 2016. Our analysis contests the prominent narrative that women are voluntarily dropping out of the labor force due to an increase in household income and conservative social norms. Our results suggest that India needs to focus more on creating jobs for women to retain them in the labor force.
Keywords: J23; J71; J16; O53; 330; female labour force participation rate; employment; social norms; India; labour demand